Análisis, diseño, desarrollo e implementación de políticas y procedimientos para la gestión de los servidores. Caso de estudio: Centro de Investigación IDE-GEOCA. - Jiménez Erazo, Darwin Ramiro (2016)
This project is a case study, where we do an analysis of security by opensource tools, applying OSSTMM and ethical hacking methodology, allowing to identify vulnerabilities in the infrastructure and showing corresponding to each mitigations, defining a scheme basis for the implementation of security policies for the IDE-IA-GEOCA..research..center.